Identifying emergency nurses' knowledge on disaster management and its predictor factor - Ahayalimudin, Nurul'ain (2013)
Introduction: As front liners, emergency nurse (EN) plays important roles in handling disaster and it became crucial to equip them with fundamental knowledge on disaster management. With the escalating number of disaster occurrence worldwide, it will assist them in providing emergency care to the affected population thus prepared them to facing disasters and its aftermath. Objective: The aim is to determine ENs’ knowledge and identifying its predictor factor. Methodology: This cross-sectional study using questionnaire and distributed to randomly selected 132 ENs. Results: The study shows the ENs identified as having inadequate know ledge in disaster management. Involvement of EN in the disaster response showed significant value (χ2=4.096, p-value=0.043) and those who had attended disaster training also illustrated significant value (χ2=12.438, p-value=0.000). The analysis continued with multiple logistic regression where the results shows involvement of EN is not a predictor factor to their adequacy of knowledge. Instead, EN who have attended disaster training showed it became a predictor factor (p< 0.01, AOR=3.807, 95% CI=1.584-9.153) where those who attended the disaster training is four times more likely to have ad equate knowledge in disaster management. Conclusion: It has been proven that adequacy of knowledge is driven by attending disaster t raining. Thus, it is paramount for organization to conduct disaster training activities to improve knowledge, further improve their preparedness upon disaster events. Keywords: disaster management; disaster nursing; emergency nurse; disaster knowledge; disaster training